Generic methodology to prevent food contamination by soil born legacy POPs in free range livestock - Farida Amutova; Matthieu Delannoy; Araylym Akhatzhanova; Nurlan Akhmetsadykov; Gaukhar Konuspayeva; Stefan Jurjanz (Heliyon, 2024)
Government monitoring commonly includes regulating POPs in animal feed and products of animal origin, with many countries setting Maximum Residue Levels (MRLs) to ensure safe tolerable concentrations. However, these MRLs do not address the presence of most POP families in soil, where concentrations can be much higher due to the contaminants' strong affinity and persistence in comparison to other environmental matrices. Extensive damage to food and production systems during a pollution incident causing soil contamination by POPs lead to severe economic and social consequences for the affected area. To mitigate these effects, it is crucial to implement necessary measures for consumer protection while also focusing on rehabilitating conditions for food production, tailored to both commercial farms and private holders. In this context, the present work aims to develop and test a methodology for assessing the tolerable concentration of the most cancerogenic legacy POPs in soil for various livestock animals in diverse rearing systems ensuring the safety of food of animal origin. Therefore, we summarize existing knowledge about the risk of POP transfer in different livestock breeding systems via soil exposure, and modeling via a backward calculation from the MRLs the corresponding tolerable quantity of POPs that may be ingested by animals in the considered rearing system. Results of these simulations showed that soil ingestion is a predominant contamination pathway, which is a central factor in the risk assessment of POP exposure on livestock farms, especially in free-range systems. In field conditions of POP exposure, low productive animals may be more susceptible to uptake through soil than high-yielding animals, even if the feed respected MRLs. Results show that PCDD/Fs revealed the lowest security ratio for low productive dairy cows (1.5) compared to high productive ones (52). Laying hens with a productivity of 45% show also as a high sensitivity to POPs exposure via soil ingestion. Indeed, their security ratio for PCDD/Fs, lindane and DDT were 3, 2 and 1, respectively. In perspective, proposed methodology can be adapted for assessing the risk of industrial POPs newly listed in the Stockholm Convention. In practice, it could be useful for food producers to apprehend their own risk of chemical contamination.